2011
DOI: 10.1136/bjsports-2011-090606.65
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of cross country skiing injuries

Abstract: There is little literature about the epidemiology of injuries sustained while conducting cross country skiing due to the disparate nature of these athletes. The Royal Marines regularly deploys to Norway to conduct cross country ski-training and cold weather warfare training which presents a unique opportunity to analyse injuries sustained while conducting this sport. A total of 1200 personnel deployed to Norway in 2010 over a 14 week period. Patients who sustained injuries who were unable to continue training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Shoulder injuries do not occur as frequently as lower limb injuries within trained military populations. However, it does appear to be unique to this training environment; Howes et al 3 similarly identified the anterior shoulder as a common injury location during Cold Weather Warfare training. Although specific mechanisms of injury were not analysed as part of this study, anecdotal evidence from the Forward Rehabilitation Team suggest that shoulder injuries tended to occur during high-velocity falls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shoulder injuries do not occur as frequently as lower limb injuries within trained military populations. However, it does appear to be unique to this training environment; Howes et al 3 similarly identified the anterior shoulder as a common injury location during Cold Weather Warfare training. Although specific mechanisms of injury were not analysed as part of this study, anecdotal evidence from the Forward Rehabilitation Team suggest that shoulder injuries tended to occur during high-velocity falls.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether this is due to skiing competency, general conditioning or additional environmental factors. Findings by Howes et al 3 suggest that skiing competency is associated with injury risk; the highest injury rates accompanied the rapid transition from non-skier to skiing with a bergen and weapon. It is also widely accepted that poor physical fitness is associated with increased risk of musculoskeletal injury 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation